(3eSdc GdnOQjf aj Md GdfjQjfs - (3CMeO Hf ehSi Hf YHO GdZaGQs
(3ChdgG (B:s
(3HYO GdOjHGLI (B: (3dGjNai Ydi ef eGQS CYeGd GdJbhje Cfg djS ai Md GdSHYI CMSf hdG CSgd ef GdJYGOjd GdeMdhdI GdeSeGg HGdOQ GdfXje ai Md GdJbhje s
(3BNQgG (B:s
(3hdh Yed eKd Pdc ai GdNeSI GdHGbjI dcGf MSfkG dcf jMJGL MjfFP Edi UaMGJ cKjQI hGddg CYde s
(3Vef eLehY , JQJjHgG (B: (3ef U (B1 - (3U(B90s
(3CMeO Hf ehSi Hf YHO GdZaGQ ceaSQ cJGH GdebfY ai Yde GdLHQ hGdebGHdI dTgGH GdOjf CMeO Hf eMeO Hf GdgGFe GdeJhai (B815 (3g`s
(3Cda SfI (B1004 (3gLQjIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3HQhcdeGf edMb (B- (3GdLRA (B2 - (3U (B155 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B3 - (3bSe (B1 - (3U (B63 s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQGdcJH GdeUQjI (B((3ejbGJ (B131) s
Keywords: (3Gdadcs